The relations between helicobacter pylori infection and gastric emptying time - T. SARIÇAM; E. VARDARELİ and Y. AKGÜN and N. E. VARDARELİ and Y. KİŞİOĞLU and; ÜNEY and; NTOK and; RENOĞLU (Turkish Journal of Gastroenterology, 2020)
-